Identification of introgressed line of BC1F1 from malaysian rice variety / Nur Aqilah Alias - Alias, Nur Aqilah (Faculty of Applied Sciences, 2015)
Rice blast disease is mostly caused by the fungus, Magnaporthe oryzae. Markerassisted backcrossing (MAB) is one of the reasonable approaches to develop a new resistant variety to confront with this challenge. The objective of the study is to identify the introgressed lines from BC1F1 population. A total of 80 seeds from BC1F1 families were obtained from Agrotechnology and Bioprocess Division, Malaysian Nuclear Agency, Bangi, Selangor, Malaysia. Based on the result there are 82.5% of seeds were successfully germinated meanwhile 17.5% seeds were unsuccessfully germinated. DNA was extracted by following the modified CTAB method. PCR analysis showed a pattern of band generated by using RM413 and RM206 primers. Marker RM 413 was tightly linked with pi-21 demonstrated 4 heterozygous (score as “H”) out of 18 backcrossed plants. RM 413 marker can be further used as a foreground marker selection in future generation in development of rice blast resistant variety in Malaysia.